The Role of Know About Business (Kab) Entrepreneurship Training in Creating Entrepreneurship Skills in Trainees of Technical and Vocational Training Centers in Sistan & Baluchestan - Abdolali Keshtegar (Journal of Global Pharma Technology, 2018)
The role of training in promotion of entrepreneurship attitudes and behaviors has widely been taken into account nowadays. Population growth in developing countries has ended in a reduction in resources and facilities along with appearance of new social and economic requirements in these countries, and all of such needs have attracted the attention of institutions and authorities for periodical solutions. The purpose of this study was to explain the role of KAB in creating entrepreneurial skills of trainees in Technical and Vocational Training Centers in Sistan & Baluchestan. The study was applied according to the purpose. Furthermore, as the present study dealt with the feasibility of training entrepreneurship skills, the method was descriptive-survey. The population was all 290 students of Technical and Vocational Training Centers in Sistan & Baluchestan. Using Morgan table to determine the sample size, we selected 165 people as the sample. The sampling method used was simple random method, as each trainee had the chance to be selected as the sample. Studying the related documents and a researcher-made questionnaire were used to collect data in this study, whose validity has been confirmed by professors, experts, and reliability by Cronbach's alpha. Descriptive and inferential statistics were used for data analysis. Descriptive statistics were used for collection and classification of demographic data; the inferential statistics were used for rejection or confirmation of the hypotheses; and statistical tests such as univariate t-test and Friedman test were used. SPSS20 was used for data analysis. The results showed that entrepreneurship training based on KAB model had a positive effect on entrepreneurial skills (technical, personal and managerial).Keywords: Entrepreneurship training, KAB model, Entrepreneurial skills, Trainee, Technical and vocational.